DINAMIKA MINERAL'NOY PLOTNOSTI KOSTI U RETsIPIENTOV POSLE PERESADKI PEChENI - Ermakova, I P; Moysyuk, Ya G; Buzulina, V P; Koliashvili, T K; Yaroshenko, E B; Kornilov, M N; Pronchenko, I A; Shmerko, N P (Osteoporoz i osteopatii, 2009)
Axial and periferal bone mineral density (BMD) was estimated by DXA twice within 1-47 months in 16 patients following orthotopic liver transplantation (OLT). Osteoporosis and osteopenia of lumbar spine and hip were identified in the first examination of all 9 recipients (group 1) with primary biliary cirrhosis (PBC) and in 5 out of 7 (71%) patients with viral hepatitic cirrhosis (group 2). Recipients which were firstly examined within 1-7 months following OLT (subgroups 1A, 2A) through 9±2.8 months showed in 1A axial BMD elevation (on 20.7+13.2% ; P=0.024) and in 2A axial so as hip BMD elevation (on 10.5+2.7%;P=0.001 and 8.1+5.9%;P< 0.05). Recipients which were examined later 18 months after OLT demonstrated no increase in BMD (subgroups 1B and 2B). Moreover two of them with PBC showed decrease in BMD, probably, as a result of transplant dysfunction and immunosuppression with glucocorticoids.